Monitoring and Evaluation Techniques and Project Performance of Internally Displaced Persons’ (IDPs) Project: A Case of Danwadaag in Mogadishu Somalia (American Journal of Arts and Human Science, 2025)
The study investigated on the influence of Monitoring and Evaluation Technique on Internally Displaced People on Project Performance with specific on Danwadaag project in Mogadishu Somalia. To examine the effects of Critical Path Identification on Danwadaag Project Performance, to evaluate the effects of Critical Task Scheduling on Danwadaag Project Performance and to investigate effects of Critical Risk Allocation on Danwadaag Project Performance. The study analyzed through two key theories: the Theory of Constraints (TOC) and the Results-Based Management (RBM) approach. The study employed descriptive correlation research design. The study population comprised of 260 subjects, from which a sample size of 158 was selected according to Kothari, 2004, out of whom 128 fully participated in the study, indicating a response rate of 81%. The study used both qualitative and quantitative techniques to collect and analyse data. The findings indicate that Critical Path Identification (CPI) has a significant positive impact on the performance 37.5% while Critical Task Scheduling (CTS) significantly enhances the performance 65.3% and Critical Risk Allocation (CRA) has had a mixed impact on the performance 44.9%. The study concludes that Critical Path Identification (CPI) significantly enhances the performance of the Danwadaag Project by improving task scheduling, coordination, project timelines, and resource management. Similarly, Critical Task Scheduling (CTS) positively impacts project performance by enhancing timeline accuracy, resource allocation, and overall project outcomes. However, Critical Risk Allocation (CRA) demonstrates a mixed influence, suggesting that its effective implementation in planning, monitoring, coordination, and resource allocation can improve project outcomes, though uncertainties about its effectiveness remain. The researcher recommends that the Danwadaag Project management should ensure the full integration of Critical Path Identification (CPI) by involving all key stakeholders, including project team members and external consultants, in task scheduling and resource coordination. The researcher further recommended that the Danwadaag project should prioritize the implementation of Critical Task Scheduling (CTS) by involving all relevant stakeholders, including project teams and coordinators, in the scheduling process. While CRA shows potential for improving project outcomes through risk mitigation, the study acknowledges its limitations and offers recommendations for better implementation. The future studies could assess the role of technology in enhancing the implementation of CPI, CTS, and CRA.